(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The present study investigated the factors influencing faculty satisfaction within higher education institutions. A quantitative survey with 30 items was administered online to faculty members (n=72) from diverse disciplines and institutional roles. Specifically, the study examined the effects of top-down leadership, hierarchical organizational culture, and the current challenges faced by academic institutions. The results showed that faculty satisfaction was significantly influenced by the leadership style at the institutional level while institutions with rigid hierarchical cultures tended to have lower faculty satisfaction. The study also identified several challenges faced by academic institutions, including budget constraints, increased workload, and shifting educational paradigms. These challenges also directly impacted faculty satisfaction in a negative way. In conclusion, to enhance faculty satisfaction, institutions should foster transparent leadership, promote a participatory organizational culture, and proactively address the challenges posed by the evolving higher education landscape.